Eclips : Tentoonstelling rond het verdwijnen - Van Bellingen, Stef; Helsen, Ludo; Neutjens, Clem; Cultuurcentrum Ter Dilft, Bornem; Hof Van Coolhem, Puurs; voormalig zwembad De Schalk, Willebroek (Antwerpen : [s.n.], 2004)
Baumgärtner, Klaus ; Clignett, Robine ; Colson, Vaast ; Cotteleer, Anton ; Delestinne, Jan ; De Waele, Leen ; De Zutter, Bart ; Garabedian, Mekhitar ; Gillen, Tina ; Ghekiere, Joris ; Goiris, Geert ; Hubert, Gauthier ; Harris, Pat ; Hullegie, Nick ; Ingimarsdottir, Gudny-Rosa ; et al.
Cultuurcentrum Ter Dilft, Bornem / Hof Van Coolhem, Puurs / voormalig zwembad De Schalk, Willebroek / 2004
kunstcatalogus